Study of Static Under Frequency Load Shedding On IEEE 3 Generators 9 Bus System Caused of Transient Condition - Sulistiawati, Irrine Budi; Priasmoro, Aga Dia; Lomi, Abraham; Priyadi, Ardyono (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Electrical energy supply at generator must increase equals with the addition of load in power system. Disturbance in a system causes the system to easily turn into transient condition. This research will be performed at an IEEE 3 generator 9 bus system, where loss of generator disturbance occurs because of 3 phase short circuit in bus 3. When 3 phase fault happens, the frequency becomes 52 Hz, while the voltage becomes 161 KV or 0.7 p.u to save the system from damaged because the frequency increment, we have to release generator to decrease the frequency system. After generator was released, frequency decrease to 42.5 Hz while voltage turn to 207 KV or 0.9 p.u respectively. As a result, it was obtained that load shedding time is at fourth second with the load must be released is 92,64 MW. After load shedding, frequency becomes 49.13 Hz with frequency increase percentage as much as 13%, while the voltage becomes 241 KV or 1.049 p.u, with voltage increase percentage as much as 14.9%.